Green Light Photoelectrocatalysis with Sulfur-Doped Carbon Nitride: Using Triazole-Purpald for Enhanced Benzylamine Oxidation and Oxygen Evolution Reactions - Jerigova, Maria; Markushyna, Yevheniia; Teixeira, Ivo F.; Badamdorj, Bolortuya; Isaacs, Mark; Cruz, Daniel; Lauermann, Iver; Muñoz-Márquez, Miguel Ángel; Tarakina, Nadezda V.; López-Salas, Nieves; Savateev, Oleksandr; Jiménez Calvo, Pablo (Advanced Science, 2023)
Materials dictate carbon neutral industrial chemical processes. Visible-light photoelectrocatalysts from abundant resources will play a key role in exploiting solar irradiation. Anionic doping via pre-organization of precursors and further co-polymerization creates tuneable semiconductors. Triazole derivative-purpald, an unexplored precursor with sulfur (S) container, combined in different initial ratios with melamine during one solid-state polycondensation with two thermal steps yields hybrid S-doped carbon nitrides (C3N4). The series of S-doped/C3N4-based materials show enhanced optical, electronic, structural, textural, and morphological properties and exhibit higher performance in organic benzylamine photooxidation, oxygen evolution, and similar energy storage (capacitor brief investigation). 50M-50P exhibits the highest photooxidation conversion (84 ± 3%) of benzylamine to imine at 535 nm – green light for 48 h, due to a discrete shoulder (≈700) nm, high sulfur content, preservation of crystal size, new intraband energy states, structural defects by layer distortion, and 10–16 nm pores with arbitrary depth. This work innovates by studying the concomitant relationships between: 1) the precursor decomposition while C3N4 is formed, 2) the insertion of S impurities, 3) the S-doped C3N4 property-activity relationships, and 4) combinatorial surface, bulk, structural, optical, and electronic characterization analysis. This work contributes to the development of disordered long-visible-light photocatalysts for solar energy conversion and storage.
CRIS-Team Scopus Importer:2023-03-03
Keywords: benzylamine photooxidation; disordered carbon nitride; photoelectrocatalysts; purpald; sulfur doping